Using 'Foundation'as Inculturation Hermeneutic in a World Church: Did Rahner Validate Lonergan?. (20th January 2012) - Orji, Cyril
<x xml:space="preserve">Abstract</x> Lonergan writes both of a foundation for human knowing as well as of a functional specialty he termed 'foundations'. Neither of these is the same as 'foundation' as the term is used by nonfoundationalists. Lack of clarity and differentiation regarding what is meant by 'foundationalism' sometimes informs the perception that Lonergan is a foundationalist. The burden of this essay is to show that Lonergan's philosophical and theological thought, as well as his use of the term 'foundations', fall awkwardly, if at all, under anti‐foundationalist strictures. There is a need to clarify and differentiate a range of terms and concepts in this regard. Lonergan shares with anti‐foundationalists the rejection of ocular metaphors and other naïve approaches to human knowing. Lonergan's own search for 'foundations', which I argue is critical for a world Church consciousness and meets the Rahner‐test for a world Church, is part of an overall project to situate knowing within identifiable, recurring patterns in the operations of human consciousness.